2010
DOI: 10.1089/hyb.2010.0009
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of a Monoclonal Antibody Against Spike Protein of Transmissible Gastroenteritis Virus

Abstract: Transmissible gastroenteritis virus (TGEV) is a member of coronaviruses. The viral spike (S) protein mediates the interaction between TGEV and its susceptible cells. Here, we expressed a truncated gene encoding the N terminal half of TGEV S gene (designated S1 gene) in a prokaryotic system. The resulting S1 protein was used to immunize BALB/c mice followed by the generation of a monoclonal antibody (MAb). A generated MAb (7F9) was identified by ELISA and the chromosome number of the hybridoma cell was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The E. coli system has advantages such as low cost, high production, and manipulation convenience, (14) and recently, we have expressed several heterologous proteins in this system successfully. (15)(16)(17)(18)(19) The SDS-PAGE showed that pIL-18 protein is approximately 25 kDa and the pIL-18 accumulated in the bacteria as inclusion bodies (Fig. 2).…”
Section: Expression and Purification Of Pil-18mentioning
confidence: 97%
See 1 more Smart Citation
“…The E. coli system has advantages such as low cost, high production, and manipulation convenience, (14) and recently, we have expressed several heterologous proteins in this system successfully. (15)(16)(17)(18)(19) The SDS-PAGE showed that pIL-18 protein is approximately 25 kDa and the pIL-18 accumulated in the bacteria as inclusion bodies (Fig. 2).…”
Section: Expression and Purification Of Pil-18mentioning
confidence: 97%
“…Previously, we have purified several inclusion body proteins from bacteria using the gel-purification method. (15)(16)(17)(18)(19) However, the purified protein was denatured and subsequent renaturation is required in order to get a biologically active protein. In this study, we utilized the fused Histidine (His)-tag in the vector to purify the pIL-18 using a Ni-NTA affinity column.…”
Section: Expression and Purification Of Pil-18mentioning
confidence: 99%
“…The chromosome number of hybridoma cells was analyzed by the conventional method using colchicines (Sigma-Aldrich) with the control of SP2/0 cells. (13,14) The stability of passage and cryopreservation was also measured by conventional techniques. (13,15) The ascites of MAb against GoIgCL was prepared using standard procedures as described previously (16) and purified by affinity chromatography using Protein G (Genscript).…”
Section: Cell Fusionmentioning
confidence: 99%
“…Our previous and current results confirm that the bacterially expressed heterologous proteins are functional immunogens for generating both monoclonal and polyclonal antibodies. (22)(23)(24)(25)28) Biological activity of the SARS-CoV S1…”
Section: Figmentioning
confidence: 99%